Genomics of cultivated palms - Arunachalam, V. (Amsterdam ; Boston : Elsevier, 2011)
Bioinformatics offers novel tools and resources to analyze plant genomes and genes. The complete genomes of two important commercial palms (dates and oil palm) have recently been sequenced. This offers scope for many computational tools to decipher the synteny, collinearity and common and unique genes of palms. This book reviews the latest developments in this field.
Incluye referencias bibliográficas
Keywords: PALMAS -- PROPAGACION